Grappling climate change in Southern Zimbabwe the experience of Bakalanga minority farmers. - Matsa, Mark; Simphiwe, M. (Sacha & Diamond Publishers., 2016)
The struggle of minority groups in response to climate change and its environmental consequences arc hardly documented. This (taper reflects on adaptation strategies of BaKalanga minority farmer communities to climate change in Bulilima district of southern Zimbabwe. Questionnaires were administered to randomly selected respondents by age-group 60 and above and to farmers who have stayed in the district for more than 30 years. These were deemed to have lived tn the district long enough to have noticed meaningful and reliable climatic and environmental changes. Interviews were conducted with key respondents among them chiefs, ward councillors. District Chief Executive Officer, District Chief AGRITEX Officer and community elders. Focus group discussions were conducted in different wards across the district. Results reveal that Bulilima District is experiencing significant climate change-inflicted environmental changes which affect the district's traditional livelihood safety nets. The environment alone can no longer support the community as before. Some families have since abandoned crop farming and are now relying on handouts from NGOs.Government and remittances from the Diaspora. Basing on Bulilima's comparatively high number of cattle, the study recommends that a beef industry be established in Plumtree town to boost the district's rural economy. Bigger dams should be built along Tekwane and Manzamnyama Rivers to provide water for people and livestock and to sustain irrigation schemes. Some farms acquired by government during the fast-track land reform programme should be padlocked and reserved strictly for dry .season grazing to reduce livestock losses to drought.